Perceived Preparedness for the Clinical Practice Among Medical Interns: A Cross-Sectional Study - Sharief WM; Mahdy NH; Al-Eraky M (Advances in Medical Education and Practice)
Wadeia Mohammad Sharief,1 Nehad Hassan Mahdy,1 Mohamed Al-Eraky2 1Medical Education & Research Department, Dubai Health Authority, Dubai, United Arab Emirates; 2Health Professions Education Department, Gulf Medical University (GMU), Ajman, United Arab EmiratesCorrespondence: Wadeia Mohammad Sharief, Medical Education & Research Department, Dubai Health Authority, Oud Maitha Road, Po box-4545, Dubai, United Arab Emirates, Tel +971558876136, Email wmAbdulRahim@dha.gov.aeBackground: Measurement of medical graduates’ perception of their internship program can help to improve the program to guarantee the general satisfaction of medical interns and enhance their clinical training.Objective: To evaluate the medical interns’ perceived preparedness for clinical practice and investigate the contributing elements.Method: The study was carried out to include 109 medical interns. Assessment preparedness for hospital practice questionnaire in Hospitals was used.Results: For clinical practice, the vast majority of participants (81.7%) were either fully or very well prepared. However, no statistically significant relationship was observed between the intern characteristics and preparedness level. It was found that the interns were not well prepared regarding handling emergencies, dealing with dying patients (44%), inserting an intravenous line (35.8%), conducting a digital-rectal examination (31.2%), as well as speaking with the social worker about the patient (29%). Males scored significantly higher than females regarding the interpersonal domain.Conclusion & recommendations: The results revealed that most interns were adequately trained for their clinical experiences. More emphasis on training in emergencies, catheterization, insertion of intravenous lines, and dealing with dying patients is required, in addition to continuous assessment of the interns after each clinical rotation to discover the areas of weakness.Keywords: perceived readiness, clinical practice, medical interns